Prostate Abscess Caused by Community-Acquired Methicillin-Resistant - Asad Ullah MD; Zeeshan Khakwani MD; Hassan Mehmood MD (SAGE Publishing, 2018)
A 60-year-old male presented with complaints of fever, chills, cough, and shortness of breath. He denied abdominal pain, urgency, dysuria, or hematuria. His laboratory data revealed an elevated white blood cell count and lactic acid, and one set of blood culture stained positive for gram-positive cocci. He was empirically started on intravenous antibiotics. On the next hospital day, the patient complained of hematuria and lower abdominal discomfort. A computed tomography scan of his abdomen and pelvis was obtained that revealed a focal hypodensity relating to prostate abscess, which was subsequently confirmed on magnetic resonance imaging of the prostate. Final report of blood cultures stated methicillin-resistant Staphylococcus aureus . He was treated with intravenous vancomycin and transurethral resection and deroofing of the prostate gland with drainage that resulted in complete resolution of his symptoms.